Interim interdicts and their effect on the governance of electricity supply : the role of section 30 of the South African Electricity Regulation Act in dispute resolution - Gerber, Leonardus (University of Pretoria, 2024)
Mini Dissertation (LLM(Extractive Industry Law in Africa))--University of Pretoria, 2023.